Percutaneous heart valves demonstrating long‐term durability: A case series of Melody valves in the pulmonary position lasting up to 19 years. Issue 2 (10th January 2023) - MacDonald, Simon T.; Bhan, Amit; Khambadkone, Sachin; Mullen, Michael
Abstract: It is uncertain how long catheter delivered percutaneous heart valves may last. In congenital cardiology, stenosis and regurgitation of right ventricular to pulmonary artery conduits and valves is common, leading to repeated operations for young patients with concomitant mortality and morbidity. It has also been unclear whether percutaneous pulmonary valves last as long as surgical pulmonary valves. When the current generation of the percutaneous pulmonary valve was first implanted in the United Kingdom from 2003, randomized trials were initially not performed, decided on a case‐by‐case basis in congenital cardiology, nor long‐term registries kept. We describe three cases where such percutaneous heart valves have lasted up to 19 years. All valves were working without significant stenosis and minor degrees of regurgitation on long‐term echocardiographic follow‐up, patients being asymptomatic. This demonstrates that percutaneous pulmonary valves can achieve long‐term durability and may prevent the need for otherwise high‐risk surgery in congenital cardiac patients.